Management of patients with endometriosis and infertility: laparoscopic treatment and spontaneous pregnancy rate - Rodríguez, Yanina (2024)
Objective: To evaluate factors involved in spontaneous pregnancy rate after surgery for endometriosis in patients with endometriosis and infertility.Methods: This retrospective study spanned from 2014 to 2020 and included a follow-up period of two years of patients with endometriosis-related infertility who underwent laparoscopic surgery. Women aged 25 to 43 years with patent tubes, no/mild male factor and no other infertility factors were selected and grouped according to fertility management as follows: patients immediately prescribed ART (16.5%, ART-p); patients who chose not to undergo ART (83.5%) and achieved spontaneous pregnancy (71.8% SP-p); and patients who first chose not to undergo ART but had it subsequently (28.2%, NSP-p).Results: A total of 200 patients were analyzed. Of the 167 patients who waited for spontaneous pregnancy, 71.8% achieved it. We observed a tendency of higher endometriosis ASRM scores in the ART-p group compared with patients who waited for spontaneous pregnancy, and lower scores in individuals that achieved spontaneous pregnancy. When we looked at how long it took to achieve pregnancy, we found that individuals in the SP-p group achieved pregnancy in 5.7 months, while subjects in the NSP-p group took 1.8 times longer than their peers in the SP-p group (p<0.001). However, once prescribed ART, the individuals in the NSP-p group achieved pregnancy within a similar time when compared with subjects in the SP-p group. In order to identify individuals that might benefit from ART early on, we performed a multivariable analysis and developed a decision tree (81.3% accuracy and 53.3% sensitivity).Conclusions: The present results indicated that, after surgery, the majority of patients achieved spontaneous pregnancy. The decision tree proposed in this study allows the early identification of patients who might require ART, thus decreasing the time between surgery and pregnancy and improving overall outcomes.